2012
DOI: 10.1002/hep.24652
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Established Hepatocellular Carcinoma Is Induced by Chemoimmunotherapy in An Orthotopic Murine Model

Abstract: The high rate of mortality and frequent incidence of recurrence associated with hepatocellular carcinoma (HCC) reveal the need for new therapeutic approaches. In this report, we evaluated the efficacy of a novel chemo-immunotherapeutic strategy to control HCC and investigated the underlying mechanism that increased the antitumor immune response. We developed a novel orthotopic mouse model of HCC through seeding of tumorigenic hepatocytes from SV40 T antigen (Tag) transgenic MTD2 mice into the livers of syngene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 30 publications
3
54
0
1
Order By: Relevance
“…Avella et al [37] reported that STAT3 can be one of the targets of chemoimmunotherapies. In our study, S3I-201 inhibited IL-6-induced STAT3 phosphorylation in vitro and decreased cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Avella et al [37] reported that STAT3 can be one of the targets of chemoimmunotherapies. In our study, S3I-201 inhibited IL-6-induced STAT3 phosphorylation in vitro and decreased cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…We previously used intrasplenic (ISPL) inoculation of histologically normal hepatocytes from MTD2 mice into immunocompetent wild type mice to generate an orthotopic HCC model, but this model lacked the element of liver fibrosis/cirrhosis which is present in the vast majority of patients with HCC[13, 14]. In the present study, IP injection of CCl 4 to induce liver fibrosis is integrated into this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical efficacy data indicate that intravenous administration of the CNL completely inhibits tumor growth and increasing survival in multiple models of HCC at a typical dose of 108 mg/m 2 (36 mg/kg) (Tagaram et al, 2011;Avella et al, 2012). In fact, in an orthotopic model of HCC in immunocompetent mice, treatment with the CNL induces tumor regression and dramatically increased survival to over 21 weeks despite termination of treatment after 6 weeks (Kester and Staveley-O'Carroll, in preparation).…”
Section: The Cnl -Mechanism Of Action and Efficacymentioning
confidence: 95%